Critical Synthesis Package: Seasonal Pattern Assessment Questionnaire (SPAQ) - Lauren Penwell-Waines; Lara Stepleman (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health sciences education of the Seasonal Pattern Assessment Questionnaire (SPAQ), and (2) a copy of the instrument developed by Norman Rosenthal, MD. The SPAQ is a brief, self-administered screening tool for seasonal affective disorder (SAD). The Seasonality Score (composed of six behavior ratings from Question 11) is used to determine the potential presence of SAD. A score of 11 or higher on this scale, along with an endorsement of at least moderate difficulties with seasonal change, indicates that further assessment should be conducted to confirm whether a diagnosis of SAD is warranted. The SPAQ is widely used in adult clinical and community samples as a screening tool for SAD. Validation studies have indicated adequate test-retest reliability and internal consistency. Several studies have been conducted with college students (including medical students) and have indicated adequate psychometric properties within these samples as well. The SPAQ may be useful in informing administrators, faculty, and student health center providers about student wellness. It also may be used in student self-assessment of intrapersonal competencies.